2022
DOI: 10.3389/fphar.2022.927179
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness of biological therapy in patients with rheumatoid arthritis: Systematic review and meta-analysis

Abstract: Background: The treatment of rheumatoid arthritis (RA), a chronic systemic inflammatory autoimmune disease, is based on disease-modifying anti-rheumatic drugs (DMARDs). Typically, it starts with conventional synthetic DMARDs (csDMARDs), and depending on the patient’s response to the treatment and the adverse events experienced, biological DMARDs (bDMARDs) are initiated. bDMARDs are more specific to inflammatory factors than csDMARDs and more efficient in inducing remission and low disease activity. Thus, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Currently, there is still a lack of information about the real-world effectiveness of TNF-α inhibitors, notwithstanding their ability to slow RA progression recorded in several randomized clinical trials [ 22 ]. Indeed, few results produced from these studies revealed that adalimumab and etanercept may be effective treatment options for patients with an inadequate response to infliximab, but they reflect a small sample size of patients that limits generalizability to real-world subjects [ 22 , 23 ]. Noteworthy, adalimumab and etanercept biosimilars demonstrated comparable efficacy to the corresponding original biologics in real-life cohorts of patients with RA [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is still a lack of information about the real-world effectiveness of TNF-α inhibitors, notwithstanding their ability to slow RA progression recorded in several randomized clinical trials [ 22 ]. Indeed, few results produced from these studies revealed that adalimumab and etanercept may be effective treatment options for patients with an inadequate response to infliximab, but they reflect a small sample size of patients that limits generalizability to real-world subjects [ 22 , 23 ]. Noteworthy, adalimumab and etanercept biosimilars demonstrated comparable efficacy to the corresponding original biologics in real-life cohorts of patients with RA [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Etanercept (ETN) is a soluble TNF receptor fusion protein that binds to and deactivates TNF, thus reducing joint inflammation [16][17][18][19][20][21][22]. It is prescribed when one or more cDMARDs fail to control the clinical symptoms of RA [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Etanercept (ETN) is a soluble TNF receptor fusion protein that binds to and deactivates TNF, thus reducing joint inflammation [16][17][18][19][20][21][22]. It is prescribed when one or more cDMARDs fail to control the clinical symptoms of RA [16][17][18][19][20][21][22]. Various systematic reviews and meta-analyses have been done in the past to check the efficacy and safety of ETN in patients with RA.…”
Section: Introductionmentioning
confidence: 99%
“… 2–4 Targeted therapy strategies have improved outcomes for many patients with reduced swollen joint counts (SJCs) and measures of inflammation such as the erythrocyte sedimentation rate (ESR) and C reactive protein (CRP) and have achieved a major goal of reducing progressive joint damage. 5 6 Unfortunately, it is now clear from multiple studies that patient global assessments, tender joint counts (TJCs) and pain scores remain high even as levels of inflammation and synovitis have reduced. 7 8 …”
Section: Introductionmentioning
confidence: 99%
“…The specific objective of this study is to accurately characterise the causes of pain in patients with RA with moderate and high disease activity (defined by DAS28(ESR)), as these patients had not achieved widely agreed goals of therapy for RA and will be considered for increased therapy. 5 6 We collected detailed clinical features, serological markers and PROMS, together with a comprehensive ultrasound (US) examination of 44 joints. It is then possible to group patients with active inflammatory joint disease detected by comprehensive US power doppler (PD) assessment and associated variables into those with possible (secondary) FM.…”
Section: Introductionmentioning
confidence: 99%